Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation. (1st April 2023) - Zhang, Qing-Yi; Tan, Jie; Huang, Kai; Nie, Rong; Feng, Zi-Yuan; Zou, Chen-Yu; Li, Qian-Jin; Chen, Jun; Sheng, Ning; Qin, Bo-Quan; Gu, Zhi-Peng; Liu, Li-Min; et al.
Abstract: To enhance the bioactivity of cellulosic derivatives has become an important strategy to promote their value for clinical applications. Herein, protocatechualdehyde (PCA), a polyphenolic molecule, was used to modify a cellulose acetate (CA) membrane by combining with metal ions to confer an immunomodulatory activity. The PCA-modified CA membrane has shown a significant radical scavenging activity, thereby suppressed the inflammatory response and created a favorable immune microenvironment for osteogenesis and mineralization. Moreover, addition of metal ions could further stimulate the osteogenic differentiation of stem cells and accelerate bone regeneration both in vitro and in vivo . This study may provide a strategy to promote the immunomodulatory activity of cellulose-based biomaterials for bone regeneration. Graphical abstract: Unlabelled Image